2019
DOI: 10.3329/bsmmuj.v12i4.44274
|View full text |Cite
|
Sign up to set email alerts
|

A 50-year-old female, diabetic patient with chest pain and dizziness

Abstract: This article has no abstract. The first 100 words appear below: A 50-year-old female got admitted on June 18, 2019 with  complaints of central chest pain for three years and dizziness for the last two months. The chest pain was compressive in nature, moderate to severe in intensity and radiating to the medial side of the left upper limb and neck. It used to get aggravated during exertion and initially relieved by taking rest but later she had to take medicine to relieve the chest pain. The pain was not a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Male occupied 88% of the total study population which reflects the male predominance for CAD [ 12 ]. Many studies have shown the significant impact of age, female gender, smoking, peripheral vascular disease, hypertension, diabetes mellitus, ischemic heart disease/myocardial infarction, and other risk factors on in-hospital mortality of patients [ 7 , 13 ] but these were well controlled before the operation in this study. Hence, the results were not statistically significant in this study.…”
Section: Discussionmentioning
confidence: 70%
“…Male occupied 88% of the total study population which reflects the male predominance for CAD [ 12 ]. Many studies have shown the significant impact of age, female gender, smoking, peripheral vascular disease, hypertension, diabetes mellitus, ischemic heart disease/myocardial infarction, and other risk factors on in-hospital mortality of patients [ 7 , 13 ] but these were well controlled before the operation in this study. Hence, the results were not statistically significant in this study.…”
Section: Discussionmentioning
confidence: 70%
“…Similarly, the prevalence of causes of glucose intolerance namely insulin resistance syndrome, diabetes, and central obesity are also increasing among young South Asians. This group of patients develops larger MI with greater myocardial damage and complications, the higher rate of clinical CAD events for a given degree of atherosclerosis, comparatively two-folds higher than the white population, and four-folds higher than the Chinese population [9] [10]. All these and the increasing prevalence of the conventional risk factors and high cholesterol where cholesterol levels similar to whites but higher than other Asian populations add to the disease burden [11].…”
Section: Discussionmentioning
confidence: 99%